2011 IEEE International Conference on Systems, Man, and Cybernetics 2011
DOI: 10.1109/icsmc.2011.6083813
|View full text |Cite
|
Sign up to set email alerts
|

Preparing drivers for dangerous situations: A critical reflection on continuous shared control

Abstract: Abstract-Shared control (also known as continuous haptic guidance or haptically active controls) has recently been introduced in car driving. With shared control, the driver receives continuous force feedback on the gas pedal or steering wheel, so that human and machine conduct the driving task simultaneously. Experiments in driving simulators have shown that shared control reduces control variability and mental workload, and improves accuracy in path tracking and car following. Crucial to road safety, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…Moreover, the automation system, on which the continuous forces are based, is often not separately evaluated and simply assumed to be perfect. Therefore, many important human-automation interaction issues remain unaddressed for haptic shared control (de Winter and Dodou 2011). For example, we hypothesize that it is easier to maintain skills and situation awareness and to catch an automation error when the continuous actions of an automatic controller is presented haptically, rather than through binary alerts, but this has not been proven yet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the automation system, on which the continuous forces are based, is often not separately evaluated and simply assumed to be perfect. Therefore, many important human-automation interaction issues remain unaddressed for haptic shared control (de Winter and Dodou 2011). For example, we hypothesize that it is easier to maintain skills and situation awareness and to catch an automation error when the continuous actions of an automatic controller is presented haptically, rather than through binary alerts, but this has not been proven yet.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an arbitrary path was chosen that was smooth but not optimized for minimum jerk [34]. In real telemanipulation situations an optimized path, completely matching with the human intention, is often not available (or hard to derive).…”
Section: Discussionmentioning
confidence: 99%
“…The number of angular reversals had a reduction of 14% (SD = 33%) with R 2 < 0.13. No evidence was found that any of the support systems resulted in overreliance or after effects [37]: Fig. 6 illustrates that the catch trials (implemented at the end of each experimental condition block) showed no significant difference compared with regular trials.…”
Section: Limitations Cross-checks and Recommendationsmentioning
confidence: 99%